Endotoxin regulates matrix genes increasing reactive oxygen species generation by intercellular communication between palmitate‐treated hepatocyte and stellate cell. Issue 1 (7th September 2018) - Dornas, Waleska; Glaise, Denise; Bodin, Aude; Sharanek, Ahmad; Burban, Audrey; Le Guillou, Dounia; Robert, Sacha; Dutertre, Stephanie; Aninat, Caroline; Corlu, Anne; Lagente, Vincent
Abstract: Previous studies have shown that gut‐derived bacterial endotoxins contribute in the progression of simple steatosis to steatohepatitis, although the mechanism(s) remains inaccurate to date. As hepatic stellate cells (HSC) play a pivotal role in the accumulation of excessive extracellular matrix (ECM), leading to collagen deposition, fibrosis, and perpetuation of inflammatory response, an in vitro model was developed to investigate the crosstalk between HSC and hepatocytes (human hepatoma cell) pretreated with palmitate. Bacterial lipopolysaccharide (LPS) stimulated HSC with phosphorylation of the p38 mitogen‐activated protein kinase/NF‐κB pathway, while several important pro‐inflammatory cytokines were upregulated in the presence of hepatocyte–HSC. Concurrently, fibrosis‐related genes were regulated by palmitate and the inflammatory effect of endotoxin where cells were more exposed or sensitive to reactive oxygen species (ROS). This interaction was accompanied by increased expression of the mitochondrial master regulator, proliferator‐activated receptor gamma coactivator alpha, and a cytoprotective effect of the agent N‐acetylcysteine suppressing ROS production, transforming growth factor‐β1, and tissue inhibitor of metalloproteinase‐1. In summary, our results demonstrate that pro‐inflammatory mediators LPS‐induced promote ECM rearrangement in hepatic cells transcriptionally committed to the regulation of genes encoding enzymes for fatty acid metabolism in light of differences that might require an alternative therapeutic approach targeting ROS regulation. Abstract : Hepatocyte–hepatic stellate cells (HSCs) crosstalk resulted in the overexpression of inflammatory genes when lipopolysaccharide (LPS)‐treated. Higher production of reactive oxygen species/proliferator‐activated receptor gamma coactivator alpha activation was found to LPS‐palmitate treatment in hepatocytes–HSCs. LPS‐palmitate induced a fibrogenic status in hepatocyte–HSCs related to oxidative stress, where tissue inhibitors of metalloproteinase 1 and transforming growth factor‐β1 were N‐acetylcysteine‐modulated.